An anti-amoebic composition - Ibrahim, Maizatul Akma (2020)
Acanthamoeba is a pathogen species responsible for causing amoebic keratitis which is considered as one of the trickiest infections to be diagnosed. In Acanthamoeba keratitis cases, the diagnosis is often difficult and delayed due to its resemblance to bacterial or fungal keratitis. Owing to failure in early diagnosis and error in prescription, the Acanthamoeba keratitis infection in the patient may risk developing into permanent blindness. Statistics show that approximately 85% of all amoebic keratitis cases were associated with contact lens users. The problem arises since current commercial contact lens solutions are reported to have lack of proper disinfectants against the Acanthamoeba species. As such, it is desirable to develop a disinfectant formulation that is suitable for use for disinfecting contact lens to minimize or prevent occurrence of Acanthamoeba keratitis in the contact lens user.